Finding The Connection of Internet and Popular Culture in 21st Century: a Descriptive Analysis - Evi Utami (KUNKUN: Journal of Multidisciplinary Research, 2024)
The evolution of the internet and digital devices has significantly transformed cultural dynamics, subtly intertwining cultural and technological aspects. Popular culture, heavily influenced by trends emerging from digital platforms, shapes modern lifestyles and mindsets. This study explores how digital advancements facilitate the global spread of popular culture, examining the complex relationship between culture, technology, and societal identity. Employing a qualitative approach through literature review, the research dissects the historical context of popular culture, its proliferation via digital means, and its impact on global societies. Popular culture, often elusive and multifaceted, challenges scholars with its conceptual complexity. The internet acts as a catalyst for cultural exchange, enabling the creation, consumption, and dissemination of cultural content in global aspect. The paper underscores the need for heightened awareness of cultural invasion and its potential to reshape national identities. Understanding the dynamic interplay between popular culture and digital platforms is crucial for navigating the cultural landscape of the 21st century